Islamic Social Services: Challenges and Opportunities (American Journal of Islam and Society, 2005)
The Sixth Annual Conference of the Islamic Social Services Association(ISSA) was held June 17-19, 2005, at Arizona State University (ASU) andthe Holiday Inn in Tempe, Arizona. Sponsors included the Department ofSocial Work, ASU at the West Campus; the School of Social Work, ASU atthe Tempe Campus; the National Association of Social Workers–Arizonachapter; the Muslim American Society–Arizona chapter; the Council onAmerican Islamic Relations–Arizona chapter; the Muslim Students Associationat ASU Tempe Campus; the Muslim Law Students’Association at ASU;the Islamic Center of the East Valley; and Global Medical Technologies.The conference and pre-conference institute continued ISSA’s mission:promoting awareness of the social welfare, mental health, and family concernsfacing Muslims in North America by educating mainstreamproviders, Muslim practitioners involved in providing human services,imams, and community leaders. The pre-conference institute’s theme was“Muslim Culture and Faith,” the title of ISSA’s anti-bias project training formainstream providers. The conference’s theme was “Islamic SocialServices: Challenges and Opportunities.”Pre-conference institute presenters Aneesah Nadir (Arizona StateUniversity and ISSA–USA) and Shahina Siddiqui (ISSA–Canada) providedinformation about Muslim culture, traditions, beliefs, the history of Islamand Muslims in North America, and social issues facing Muslims, as wellas guidelines and considerations for addressing the social issues thatMuslims’ experience. Social workers, counselors, teachers, health-care andmental-health providers from mainstream social service organizations, publicand private schools attended the pre-conference institute.Social work educators, doctoral candidates, and Muslim communitysocial service providers were among the presenters for the overall ISSA conference.Abdul Malik Mujahid (Soundvision), Omar Shahin (NationalAssociation of Imams Federation [NAIF]), Mohamed Magid (All DullesArea Muslim Society [ADAMS]) and Bonita McGee (ISSA–USA) facilitateddiscussions with imams and community leaders. This session exploredways imams can address social issues and strategies Muslim social serviceproviders can employ to help them meet the community’s social needs.While the imams identified a complex situation with a variety of problemsand solutions, it became clear that they do not have the knowledge and skillsto address the community’s many social and family issues. Opportunities forconsultation and education with imams and mosque leaders are necessary,therefore, organizations like NAIF are working with ISSA to provide this totheir members. Imams also need to be recognized as professionals with clearjob descriptions and regular (including counseling) hours. One imam is notenough; perhaps youth imams and assistant imams are needed ...